2013
DOI: 10.1002/stem.1485
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and oncogenic radiation effects on neural stem cells and their differentiating progeny in mouse cerebellum

Abstract: Neural stem cells are highly susceptible to radiogenic DNA damage, however, little is known about their mechanisms of DNA damage response (DDR) and the long-term consequences of genotoxic exposure. Patched1 heterozygous mice (Ptc1 1/2 ) provide a powerful model of medulloblastoma (MB), a frequent pediatric tumor of the cerebellum. Irradiation of newborn Ptc1 1/2 mice dramatically increases the frequency and shortens the latency of MB. In this model, we investigated the mechanisms through which multipotent neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 57 publications
(69 reference statements)
2
31
0
Order By: Relevance
“…Unsurprisingly, 455 differentially spliced exons and nearly 50 affected biological processes were identified between CON and IR-treated NSCs. Some were neural cell-related processes such as nervous system development, neuron projection development, dendrite morphogenesis, and negative regulation of astrocyte differentiation, which indicated that DNA damage could affect NSC development, consistent with the findings of a previous study [4]. Furthermore, the expected DDR-related procedures were also included, such as apoptotic signaling, regulation of cyclin-dependent protein kinase activity, and drug response pathways.…”
Section: Discussionsupporting
confidence: 87%
“…Unsurprisingly, 455 differentially spliced exons and nearly 50 affected biological processes were identified between CON and IR-treated NSCs. Some were neural cell-related processes such as nervous system development, neuron projection development, dendrite morphogenesis, and negative regulation of astrocyte differentiation, which indicated that DNA damage could affect NSC development, consistent with the findings of a previous study [4]. Furthermore, the expected DDR-related procedures were also included, such as apoptotic signaling, regulation of cyclin-dependent protein kinase activity, and drug response pathways.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, it appears that tonic activation of DNA double-strand breaks in early-born neural progenitors is linked to a progressive differentiation state of neurogenesis. In this context, neural progenitors are extremely sensitive to DNA damage, particularly at different G1 and S phases of development (McKinnon, 2013;Tanori et al, 2013). This may be attributed to the high replication rate of neural progenitors during routine neurogenesis cycles.…”
Section: Discussionmentioning
confidence: 99%
“…This susceptibility is most likely due to the high proliferative rate characteristic of NSCs. IR interferes with the embryonic development of many brain structures, such as the neocortex (3), cerebellum (4), and hippocampus (5). It has been shown that IR induces DNA doublestrand breaks, leading to microcephaly and mental retardation via activation of p53-dependent apoptosis (3).…”
mentioning
confidence: 99%